Circuit and Method for Multiphase Operation of an Electrical Machine - Austermann, Johann; Borcherding, Holger
The invention relates to a circuit and to a method for operating an electrical machine (M) connected to at least three phases (L1, L2, L3) of a power supply network by means of a frequency converter (1) that has a DC link (3), wherein, by means of a synchronous inverter (7) that is actuated by a DC chopper (6) and comprises two bridge halves switching the positive and the negative half-waves respectively, the energy generated by said machine (M) is fed back into the power supply network. According to the invention, the synchronous inverter (7) has an asymmetrical design such that, to switch the potential tapped from the DC link (3) by the DC chopper (6), switching is carried out by a first bridge half (8) that consists of thyristors (S1, S3, S5) as electronic switches, and such that the second bridge half (9) comprises reverse-blocking electronic switches (S2, S4, S6) able to be switched off.